Aritmofobia di Kalangan Mahasiswa Jurusan Bahasa dan Sosial: Kajian Neurosains - Erwin, Erwin; Rudhito, Marcellinus Andy (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Arithmophobia or Numerophobia is a person’s anxiety or fear of mathematics, numbers and arithmetic. People with symptoms of Arithmophobia will experience anxiety, worry, fear and tend to stay away from Mathematics. This study aimed to determine the description of Arithmophobia in students majoring in Language and Social Sciences based on studies from neuroscience. This study uses a quantitative descriptive approach using descriptive statistical analysis. The research subjects were 22 students using the FoMNA-Q (Fear of Mathematical, Number and Arithmetic Questionnaire) scale as a measuring tool for Arithmophobia. The results showed that there were students majoring in Language and Social Sciences with characteristics of Arithmophobia, namely the dimension of anxiety towards mathematics, with a mean value of 40.9%. Then the dimension of worrying about mathematics with a mean value of 54.5%. The dimension of fear of mathematics with a mean value of 27.3%. Moreover, the dimension of wanting to stay away from mathematics with a mean of 31.8%.